An investigation into the catalytic activity of porcine cytochrome P450 17α-hydroxylase/17,20-lyase - Fox, Cheryl-Leigh (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc) Stellenbosch University, 2014